Eruca sativa and Raphanus sativus oils Enhance Hepatic and Renal Tissues Regeneration in White Mice - Amal Kamil (Al-Mustansiriyah Journal of Science)
Regeneration is a process of tissue repairing in the body, and according to this process the cells of the body are divided into three types; labile, stable and permanent cells. Objectives: The aims of this study are to evaluate the ability of two herbal seed oils (Eruca sativa and Raphanus sativus) to enhance regeneration and repair in the liver and kidney in the irradiated mice. And to investigate which herbal oil is more effective. Method: Four groups of mice were used in this study. The first three groups were exposed to radiation while the fourth was used as a control. After irradiation the first and second groups were treated with local Eruca sativa and Raphanus sativus oils respectively. While the third group used as a control. Then histopathological investigation was done. Results: Histopathological examination in irradiated groups exhibited that both seed oils could induce regeneration in both hepatic and renal tissues but the activity of Raphanus sativus oil was more effective than Eruca sativa especially in renal tissue. Meanwhile, poor regeneration process appeared in the third group (control). Conclusion: Both local herbal oils had ability to enhance regeneration in the examined tissues but R. sativus seed oil exerted more activity than E. sativa seed oil.